2011
DOI: 10.3402/meo.v16i0.6035
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration: three best practice models of interprofessional education

Abstract: Interprofessional education is a collaborative approach to develop healthcare students as future interprofessional team members and a recommendation suggested by the Institute of Medicine. Complex medical issues can be best addressed by interprofessional teams. Training future healthcare providers to work in such teams will help facilitate this model resulting in improved healthcare outcomes for patients. In this paper, three universities, the Rosalind Franklin University of Medicine and Science, the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
605
1
29

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 792 publications
(643 citation statements)
references
References 18 publications
8
605
1
29
Order By: Relevance
“…[7] Training future health care providers to work in IP teams will improve the health care outcomes of the patients. [21]…”
Section: Discussionmentioning
confidence: 99%
“…[7] Training future health care providers to work in IP teams will improve the health care outcomes of the patients. [21]…”
Section: Discussionmentioning
confidence: 99%
“…[36,37] Research has shown that the time spent together with other professionals in a simulated learning environment can lead to sharing of knowledge, skills and values and increase mutual appreciation. [38] Respondents in this study found multiprofessional simulation education especially useful in learning to deal with acute, recurring and infrequent situations. It was further discovered that students appreciated the evolving shared competence, that is, sharing one's knowledge, learning from others, learning together and learning teamwork skills.…”
Section: Discussionmentioning
confidence: 99%
“…Transactional dialogue ensures that each group understands each other's workplace culture and dominant language with a sharing of viewpoints and interpretations to develop a real partnership. Recognition of the tutor, and support for tutors to perform that role, is essential for supporting programmes with integrated work based learning (Pitts et al, 2001;Austin and Braidman, 2008;Bridges et al, 2011;Fullerton, Thompson and Johnson, 2013). The failure to establish this in the current programme has resulted in participants not 'buying-in' to the role of stakeholder, clearly evidenced in the academic group by 'why should we be expected to teach them that -it's something that once they are in practice they get'.…”
Section: Findings and Discussionmentioning
confidence: 99%